La geografía en un mundo postmoderno Los debates teóricos y metodológicos en el siglo XXI - Beraún Chaca, John James (2006)
The present investigation approaches two divergent tendencies that contribute inthe construction of the geography, the quantitative geography and the radicalgeography. The first one approaches the analysis of the geographical processes fromthe numeric perspective, based on the mathematics, statistic and computer science.The second tendency has a mainly social focus and it prioritizes the studies of thesocial and space inequality. However, recent studies demonstrate that it exists, betweenboth, a theoretical-methodological complement. The radical geography prioritizesthe conceptual construction and the quantitative geography the construction ofmethodologies. For it, the present study approaches the hybrid one, of theory andmethodology, resultants of the convergence of these two tendencies, the generationin new ways of analysis of the social processes and the re-definition and reconstructionof the methodological and conceptual aspect of the current geographical science.